The elite player performance plan: the impact of a new national youth development strategy on injury characteristics in a premier league - Tears, C.; Chesterton, P.; Wijnbergen, M. (Journal of Sports Sciences, 2019)
The objective of this study was to investigate the injury incidence and patterns in elite youth football at a category 1 Premier League Academy before and after the introduction of a new development strategy, the Elite Player Performance Plan (EPPP). A prospective study was performed over six consecutive seasons encompassing three years before and after the introduction of the EPPP. The findings revealed a most likely moderate increase in total exposure per player per season when the post-EPPP football exposure (640.86 ± 83.25 hours per player per year) was compared with the pre-EPPP football exposure (539.08 ± 71.59). The total injury incidence pre-EPPP was 3.0/1000 hours compared to 2.1/1000 hours post-EPPP (rate ratio 1.43). 6% of all injuries were re-injuries (20.24 ± 33.43 days) but did not result in a substantially longer absence (16.56 ± 15.77 days). The injury burden decreased for the U12-U15 from pre- to post-EPPP, whereas the injury burden increased for the U16-U18 (respectively 125 and 47% higher). These findings suggest that following the introduction of the EPPP there has been a reduction in injuries in the younger age groups U12-U15 but in the older age groups U16-U18 there has been an increase in the severity of the injuries sustained at this club.